Girls for Sale? Child Sex Ratio and Girls Trafficking in India - Nishith Prakash; Krishna Chaitanya Vadlamannati (Institute for the Study of Labor (IZA), 2014)
Illegal trafficking of women is a result of their disadvantageous position in the society that is often reflected in increasing preference for son and neglect for daughters. Multiple reports point to India as country confronted with both higher levels of illegal trafficking of girls and abnormal child sex ratios in favor of boys. In this paper we examine if a skewed sex ratio and shortage of girls is associated with their illegal trafficking in India. Using panel data of 29 Indian states from 1980-2011, we find that 100 unit increase in child sex ratio is associated with 0.635% increase in illegal trafficking of girls. We find the association to be heterogeneous by female empowerment, crime against women and party rule in the state. We find that association between child sex ratio and illegal trafficking of girls is stronger and larger in magnitude in states with greater female empowerment. Overall, it appears that the results are driven by both greater reporting and greater incidence of illegal girls trafficking. Contrary to popular belief, the results do not vary differentially by states with larger share of schedule tribe population or states bordering Nepal and Bangladesh. Our results survive variety of robustness checks.
Keywords: J10; O12; R23; Z12; 330; child sex ratio; girls trafficking; India